'Leave me alone' lesions of the petrous apex. - Moore, K R; Harnsberger, H R; Shelton, C; Davidson, H C (American Journal of Neuroradiology, 1998)
PURPOSE When troublesome MR imaging findings are noted in the petrous apex, the radiologist must determine if the area in question needs surgical therapy. Two nonsurgical entities, asymmetric fatty marrow and fluid-filled petrous air cells (trapped fluid), can be noted on conventional brain MR images and confused with pathologic lesions. Our observation that radiologists do not always confidently define the nonsurgical petrous apex lesions precipitated this investigation.METHODS Twenty-three patients with either asymmetric fatty marrow (six) or unilateral effusion in a pneumatized petrous apex (17) on MR images were studied. Eighteen patients underwent high-resolution temporal bone CT. For all patients, the medical charts were reviewed retrospectively and/or the surgical and clinical follow-up findings were reviewed with the referring physician.RESULTS In the patients with asymmetric fatty marrow, MR signal intensity followed fat on all sequences. The questioned apex in the patients with trapped fluid showed mixed MR signal characteristics (low to high T1 signal, high T2 signal). CT scans confirmed nonexpansile air-cell opacification.CONCLUSION Asymmetric fatty marrow in the petrous apex and petrous air-cell effusions have characteristic MR and CT features that facilitate their correct diagnosis. Effusions with intermediate or high T1 signal are most frequently confused with cholesterol granulomas. In those patients, long-term CT follow-up may be helpful to confirm their stability.